Kajian Estetika Tari Setra Sari karya Gugum Gumbira - Herly Merliana; Farah Nurul Azizah (Universitas Sultan Ageng Tirtayasa, 2024)
Setra Sari Dance is a Jaipongan dance repertoire by a maestro named Gugum Gumbira Tirasonjaya in 1981 as an industrial necessity at that time, namely one of the promotions of Jaipongan's cassette song entitled Serat Salira. This dance is unique and different from other Jaipongan dance works, especially in the smooth character of the movements and colors of the clothes. Therefore, the author is interested in exploring the aesthetic elements of dance, so qualitative research and Djelantik’s intrumental aesthetic theory are used with a descriptive analysis method approach that goes through stages of data mining such as literature study, observation, and data analysis. Based on the results of the analysis, it was concluded that the Setra Sari dance was formed by three main elements, namely; form, consisting of form and structure. The structure includes; choreographic structure, dance accompaniment, and make-up. Weight or content, including; atmosphere, ideas, and messages. Appearance or presentation, including; talents, skills, and means or media. These three elements are dance aesthetics that are the identity of the Setra Sari dance. Keywords: Dance Aesthetics, Setra Sari Dance, Gugum Gumbira